Newtonalized orthogonal matching pursuit for the linear frequency‐modulated pulse frequency agile radar - Jiang Zhu (Wiley, 2021)
Abstract The linear frequency‐modulated frequency agile radar (FAR) can be used for synthesizing high‐range‐resolution profiles (HRRP), and also has excellent electronic counter‐countermeasures performance. Similar to the Newtonalized orthogonal matching pursuit (NOMP) for line spectral estimation problem, the NOMP for the FAR radar termed as NOMP‐FAR is designed to process each coarse range bin to extract the HRRP and velocities of multiple targets, including the guide for determining the oversampling factor and the stopping criterion. In addition, it is shown that the target will cause false alarm in the nearby coarse range bins, and a post‐processing algorithm is proposed to suppress the ghost targets. Numerical simulations are conducted to demonstrate the effectiveness of NOMP‐FAR.